Computer analysis of nuclear track emulsion exposed to thermal neutrons and Cf source. Issue 2 (January 2016) - Mamatkulov, K Z; Ambřozová, I; Artemenkov, D A; Bradnova, V; Kamanin, D V; Kattabekov, R R; Majling, L; Marey, A; Ploc, O; Rusakova, V V; Stanoeva, R; Turek, K; et al.
Abstract: Application of the nuclear track emulsion technique (NTE) in radioactivity and nuclear fission studies is discussed. It is suggested to use a HSP-1000 automated microscope for searching for a collinear cluster tri-partition of heavy nuclei implanted in NTE. Calibrations of α-particles and ion ranges in a novel NTE are carried out. Surface exposures of NTE samples to a Cf-252 source started. Planar events containing fragments and long-range α-particles as well as fragment triples only are studied. Splittings induced by thermal neutrons are studied in boron-enriched emulsion. Use of the image recognition program "ImageJ" for obtaining characteristics of individual events and for events from the large scan area is presented.